Analysis of Legal Policy Enforcement Against Child Bullying Perpetrators (Journal of Creativity Student, 2022)
The State of Indonesia is a legal state where this is regulated in the 1945 Constitution of the Republic of Indonesia, especially in Article 1 paragraph (3). The consequence of this rule of law is that all aspects of state life are regulated in existing legal policies. This applicable law has a function as a regulator of all community actions including children. Children need special protection and enforcement within the protection of the law itself. The influence of all existing developments, including the development of science, technology, and culture, is not only felt by adults, but also by children. Along with these developments, it also does not cover the emergence of deviant behavior from minors, and one form of deviation is bullying. In Indonesia itself, cases of bullying are often found by underage children which have even been categorized as violence and bullying. Then often the perpetrator is not punished according to his actions just because he is underage, so this makes it difficult for the victim to heal the trauma because they still see the victim roaming around without proper law enforcement. For this reason, in this paper, the author will analyze how this can happen, and also how to enforce the law for the perpetrators of these minors.